Mekanisme Antibakteri Ekstrak Etanol Daun Kemangi (Ocimum basilicum L.) terhadap Salmonella typhi - Nasri Nasri; Vera Estefania Kaban; Denny Satria; Hariyadi Dharmawan Syahputra; Zulmai Rani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Infectious diseases are conditions that can be brought on by a variety of different organisms, including bacteria, viruses, fungi, and parasites. Typhoid fever is an example of an infectious disease that frequently causes the body's defenses to come under attack. The fever associated with typhoid is a leading cause of death around the world. Infection with the bacterium Salmonella typhi is considered to be one of the potential causes of typhoid fever. When antibiotics are used to treat bacterial infections, there is a risk that the bacteria will become resistant to the medication. In day-to-day life, basil leaves are utilized both as a cooked vegetable and as a fresh vegetable. The antibacterial properties of kemangi leaves have yet to be fully uncovered. The purpose of this study was to investigate the various mechanisms that are involved in antibacterial activity. These mechanisms include cell leakage, minimum inhibitory concentration, minimum killing concentration, and antibiofilm activity. The minimum inhibitory concentration (MIC) was determined with the agar diffusion method, the minimum biofilm forming concentration (MBC) was determined with the staining method, and cell leakage was determined with UV-VIS spectrophotometry at wavelengths of 260 nm (DNA) and 280 nm (protein). Additionally, the formation of anti-biofilms was determined with microtiter plates and gentian violet staining. In the moderate category, the MIC value tests showed a concentration of 0.3125% with an inhibition zone value of 6.80 0.05 mm. These results were obtained from the MIC value. Because there was no detectable bacterial growth on the streaked medium, KBM was obtained at a concentration of 10%. At wavelengths of 260 and 280 nanometers, leakage cells show absorbance absorption. The percentage of biofilm activity that is measured when the concentration is increased to 25% is 44.82%. In conclusion, the ethanol extract of basil leaves possesses a possible antibacterial mechanism against Salmonella typhi. This was discovered through testing.